Edukasi Ibu Rumah Tangga Memanfaatkan Potensi Lokal untuk Meningkatkan Imunitas Tubuh di Desa Lonjoboko Kabupaten Gowa - Nurbaeti, Nurbaeti; A. Rezky Amelia AP (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Utilization of local potential in this case is papaya fruit, both young and ripe. Not many people know about young papaya as a snack, because residents know that young papaya is only made as a vegetable. Consuming young papaya is very good for digestive health, pumping breast milk for nursing mothers. because young papaya contains vitamins and minerals that are quite complete. The participation of related parties to provide input to the community utilizes young papaya as a snack in the form of chips and can be used as a family household business. A variety of snacks in the form of healthy chips is really needed by the community, especially housewives so that the family can be healthy, considering that papaya plants are very easy to cultivate in the yard and can be harvested in a short time. The results of this activity were, (1) Increased knowledge of housewives/PKK about the benefits of papaya fruit for body health seen from the pretest 86.75% and posttest 91% (2) Community education on the importance of increasing body immunity, followed by 20 participants consisting of PKK mothers and Lonjoboko Village staff. (3) The demonstration of chips processing was attended by 16 housewives/PKK and 4 village staff by distributing household tools in the form of 10 grated sticks, 10 sticks of shavings and 10 sticks of filter countainer.